(±)-2-(2-Fluoro-[1,1′-biphenyl]-4-yl)-N-(1-phenylpropan-2-yl)propanamide - Stanimir Manolov; Iliyan Ivanov; Dimitar Bojilov (Molbank, 2022)
2-(2-fluoro-[1,1′-biphenyl]-4-yl)-N-(1-phenylpropan-2-yl)propanamide was synthesized by a reaction between amphetamine and flurbiprofen in high yields. The newly obtained hybrid molecule was fully analyzed and characterized via 1H, 13C, UV, IR, HPLC, and mass spectral data.